Constraint Management in Database Applications via Checker Framework - Asatryan, Armen J. (Mathematical Problems of Computer Science, 2024)
The paper presents concepts and ideas underlying an approach for constraint management in VLSI design database applications and designs flows. In this approach constraints are defined as scripts of EVA strongly typed scripting language and stored in meta-databases called check catalogue. Interaction of applications with check catalogue is supported by subsystem of DBMS called Checker Framework. Checker Framework provides facilities for creation, modification and deletion of the constraints and has several features that enhance the constraint management in database applications.